University-Level puppetry training (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2018)
For seventy years puppet theatre in the region of Central-Eastern Europe has been developing in a different rhythm than elsewhere. Introducing puppeteer training was a natural consequence of the establishment of institutional puppet theatres. The puppetry schools were modelled on art academies; after all, these academies had been educating artists, musicians, actors, so why not puppeteers? University-level facultiesof puppetry finally emerged in the 1950s because, so to speak, the realities of the era had demanded it. What is the situation now? Is the long-term professional training of puppeteers still interesting, useful, needed? What are the strengths and weaknesses of the system of the university-level puppeteer training?Keywords: Puppetry. Art training. Puppetry schools.